2020
DOI: 10.7124/bc.000a27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of biological activity of rhodanine-pyrazoline hybrid molecules with 2-(2,6-dichlorophenylamino)-phenylacetamide fragment

Abstract: Synthesis of new rhodanine-pyrazoline hybrid molecules with a diclofenac fragment in position 3 using the reactions of heterocyclization and aminolysis with potential antitumor and antitrypanosomal activities. Methods. Organic synthesis, NMR spectroscopy, pharmacological screening. Results. The reaction between 2-(2,6-dichloro-phenyl-amino)-phenylacetic acid hydrazide and thiocarbonyl-bis-thioglycolic acid in ethanol medium providing rhodanine derivative with fragment of the anti-inflammatory drug diclofenac i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Based on this form of furochromone, khellin with a lipophilic rhodanine structure, the discovery of even more active molecules slowing down the progression of the tumor cells could be carried out, mainly for novel anti-breast cancer agents. New 5-(3,5-diaryl-4,5-dihydropyrazol-1-ylmethylene)-2-thioxothiazolidin-4-ones with a diclofenac moiety, namely compound 30 and 31 (Figure 15), have been synthesized and evaluated for their antitumor activities [10]…”
Section: O Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this form of furochromone, khellin with a lipophilic rhodanine structure, the discovery of even more active molecules slowing down the progression of the tumor cells could be carried out, mainly for novel anti-breast cancer agents. New 5-(3,5-diaryl-4,5-dihydropyrazol-1-ylmethylene)-2-thioxothiazolidin-4-ones with a diclofenac moiety, namely compound 30 and 31 (Figure 15), have been synthesized and evaluated for their antitumor activities [10]…”
Section: O Hmentioning
confidence: 99%
“…These rhodanine-pyrazoline hybrid molecules, with a diclofenac moiety after some further modifications on pharmacophore, could potentially serve as a base for designing novel anticancer drugs. New 5-(3,5-diaryl-4,5-dihydropyrazol-1-ylmethylene)-2-thioxothiazolidin-4-ones with a diclofenac moiety, namely compound 30 and 31 (Figure 15), have been synthesized and evaluated for their antitumor activities [10]…”
Section: O Hmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale behind introducing the amino side chains into the core of neocryptolepine was justified due to their indispensable role in antiproliferative activity. On the other hand, rhodanine, 2-thioxo-4-thiazolidone C, and its analogs ( Figure 2 ) have a wide range of biological activities such as antidiabetic [ 21 ], antiviral [ 22 , 23 ], anti-inflammatory [ 24 ], antimicrobial [ 25 ], antimalarial [ 26 ], antifungal [ 27 , 28 ], anti-HIV [ 29 ], and anticancer agents [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the all-tested compounds, only Derivatives 54a-54c and 55 (Figure 23) showed % of growth inhibition more than 50% at concentration 10 µM against Dami cell line. The study conducted by Shepeta et al showed that rhodanine-pyrazoline hybrid with diclofenac moiety (56) had high effectiveness against 60 cancer cell lines (NCI DTP protocol) with a mean of GI50 = 0.71/1.09 µM and TGI = 82.95/28.46 µM [57]. Tilekar et al described series of 5-(naphtha-2-ylidene)thiazolidine-2,4-dione derivatives as simultaneously target PPARγ and HDAC (Figure 24).…”
mentioning
confidence: 99%